Hubungan Pekerjaan, Jenis Kelamin, Umur dan Aktivitas Fisik dengan Massa Otot pada Masyarakat Lhokseumawe - Wendy susri; Nora Maulina; Cut Sidrah Nadira (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Physical activity is essential for optimizing human health. According to the WHO, more than a quarter of the world's adult population (1.4 billion people) is inactive in physical activity, and this figure increased during the COVID-19 pandemic. Inactivity is one of the risk factors causing NCDs. According to the Ministry of Health, NCDs cause the deaths of 41 million people (71% of global deaths) every year, and physically active has been shown to reduce the incidence of NCDs and can increase body muscle mass as an indicator. The purpose of this study was to determine the relationship between work, gender, age, and physical activity with muscle mass in the people of Uteunkot Village, Lhokseumawe.This non- experimental study used a cross-sectional approach with a total sample of 94 samples obtained by the accidental sampling technique. Physical activity data were obtained with the 2003 IPAQ questionnaire, and the percentage of muscle mass was measured using the Tanita BC-730 scale. The results showed that the majority of respondents between the ages of 17-25, working as Civil Servants/BUMN/ BUMD, doing moderate physical activity, have a normal percentage of muscle mass, while women have low muscle mass. The conclusion of this study is that there has been no proven relationship between physical activity and muscle mass, However, a significant relationship with a strong correlation was found between sex and muscle mass in the people of Uteunkot Village, Lhokseumawe.